The effects of Energised Greens™ upon blood acid-base balance during resting conditions - Mitchell Nigel; Page Richard; Turner Mark; Siegler Jason (Taylor & Francis Group, 2011)
Abstract Background The consumption of fresh fruit & vegetable in concentrate form (FVC) have recently become an alternative approach to combating excessive renal acid loads often associated with Western Diets. Additionally, these FVC's have been purported to induce metabolic alkalosis, which perhaps may enhance the blood buffering capacity of an individual. Therefore, the aim of this preliminary study was to profile the acid-base response after ingestion of an acute dose of fruit and vegetable extract (Energised Greens™ (EG), Nottingham, UK) and compare it to a standard, low dose (0.1 g·kg-1) of sodium bicarbonate (NaHCO3). Findings As part of a randomized, cross over design participants consumed 750 mL of water with either 9 g of EG (manufacturer recommendations), 0.1 g·kg-1 of NaHCO3 or a placebo (plain flour) in opaque encapsulated pills following an overnight fast. Capillary samples were obtained and analyzed every 15 min for a period of 120 min following ingestion. Significant interactions (p < 0.01), main effects for condition (p < 0.001) and time (p < 0.001) were evident for all acid-base variables (pH, HCO3-, BE). Interactions indicated significant elevation in blood alkalosis for only the NaHCO3 condition when compared to both placebo and EG from 15 to 120 minutes. Conclusions Despite previous findings of elevated blood pH following acute mineral supplementation, manufacturer recommended doses of EG do not induce any significant changes in acid-base regulation in resting males.